Umieszczanie reklam na zabytkach - Gadecki, Bartołomiej (Studia Prawnoustrojowe, 2019)
Monuments are protected under provisions of criminal law, which are contained both in the Act on the Protection of Monuments and the Guardianship of Monuments and in the Penal Code. This article aims to examine dogmatic aspects of misdemeanour specifed in Articles 118 of the Act on the Protection of Monuments and the Guardianship of Monuments. The said Article regulates misdemeanour of placing advertisements on monuments without a permit. Placing advertisements on a monument entered into the Inventory of Monuments requires permission of the Voivodship Inspector of Monuments. Examined herein is the meaning of the following terms: “placement”, “monument entered into the Inventory of Monuments”. The conclusions are based on formal-dogmatic analysis. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">